The Fund's Income Position for FY 2013 : Midyear Update. (Policy Papers; Policy Paper ;, 2012)
This paper presents updated projections on the Fund's FY 2013 income position. The projected net income is now SDR 2.1 billion, slightly lower than the earlier projection of SDR 2.3 billion at the beginning of the year. The changes reflect lower projected disbursements under approved arrangements owing to delays in scheduled drawings and arrangements expected to expire with substantial undrawn balances, the expectation that funding of the gold endowment will not begin until FY 2014, and lower implicit returns on the Fund's interest-free resources due to the prevailing interest rate environment.